Inequality in fetal autopsy in Canada - Auger, Nathalie; Tiandrazana, Rémi- Claude; Healy-Profitós, Jessica; Costopoulos, André (Journal of health care for the poor and underserved, 2016)
Purpose. Inequality in use of fetal autopsy is poorly understood, despite the importance of autopsy in establishing the cause of stillbirth for future prevention. We examined fetal autopsy rates between linguistic minorities in Quebec, Canada, and assessed trends over three decades. Methods. Using registry data on 11,992 stillbirths from 1981–2011, we calculated fetal autopsy rates for Francophones, Anglophones, and Allophones by decade. Results. We found lower fetal autopsy rates for Allophones (54.4%) than Francophones (68.5%) and Anglophones (63.4%), but rates decreased over time for all language groups. After 2000, Allophones had 25% higher risk of non-autopsy relative to Francophones, with 8.8 fewer autopsies for every 100 stillbirths. Allophones who were not autopsied had 32% higher risk of having an undetermined cause of death. Conclusion. Inequality in use of fetal autopsy may be widespread for minorities in Canada. Efforts to decrease stillbirth in minorities may require policies to increase autopsy rates.

État de la situation et étude de modèles de soins de santé primaires offerts aux francophones vivant en situation minoritaire au Canada - Axion (2016)

Comorbidités entre maladies chroniques et problèmes de santé mentale fréquents : différences entre francophones et anglophones - Grenier, Jean; Gosselin, Dominique; Greenman, Paul. Samuel; Chomienne, Marie-Hélène; Imbeault, Pascal; Batal, Malek; Bouchard, Louise (Psy-Cause, 2016)

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Enquête sommaire sur la santé des francophones de Colombie-Britannique - RésoSanté Colombie-Britannique (2016)